Veterans Affairs Prostate Cancer Treatment Sequencing (VAPCaTS): A Real-World Evidence Study of Men with Metastatic Prostate Cancer. Issue 1 (29th January 2021) - Freedland, Stephen J.; De Hoedt, Amanda M.; DerSarkissian, Maral; Chang, Rose; Satija, Ambika; Nguyen, Catherine; Park, Suna; Aillaud, Aurore; Drea, Edward; Duh, Mei S.; Polascik, Thomas J.; Szatrowski, Ted
Abstract: Introduction: Limited real-world data are available on treatment sequences for patients with metastatic hormone-sensitive prostate cancer treated with androgen deprivation therapy plus docetaxel or abiraterone who progress to castrate resistance. Methods: Veterans Health Affairs electronic medical records were used to analyze 240 men treated for metastatic hormone-sensitive prostate cancer with androgen deprivation therapy plus either docetaxel ("docetaxel cohort, " 208 patients, selected to be overrepresented, July 2014 to August 2018) or abiraterone ("abiraterone cohort, " 32 patients, December 2016 to September 2018) who received at least 1 treatment after progressing to castrate resistance. Results: For docetaxel and abiraterone cohorts, respectively, mean age at androgen deprivation therapy initiation was 65 and 72 years, and median followup was 2.2 and 1.4 years. Overall, the maximum number of metastatic castrate resistant prostate cancer treatment lines was 6; 106 patients (44%) had 1, 71 (30%) had 2, and 63 (26%) had 3 or more lines. Most patients received an androgen receptor targeted agent for initial metastatic castrate resistant prostate cancer treatment (94% vs 78% in docetaxel vs abiraterone cohort). Androgen receptor targeted agents were given consecutively to 62% of the docetaxel cohort receiving second line therapy, and to 78% of the abiraterone cohort. Across all metastatic castrate resistant prostate cancer treatment lines 72 (30%) received a taxane (47 docetaxel and 41 cabazitaxel). Conclusions: Most patients received androgen receptor targeted agents as first metastatic castrate resistant prostate cancer treatment regardless of initial metastatic hormone-sensitive treatment. Moreover, a large proportion were treated with consecutive androgen receptor targeted agents. Given recent evidence suggesting poorer outcomes with this treatment in some patients, longer followup is needed to assess the association between treatment sequence and optimal outcomes.